Chelonoidis chilensis (Chaco Tortoise): Endoparasites - González Rivas, Cynthia Jesica (2019)
Two species of the genus Chelonoidis occur in Argentina, both of which are considered nationally endangered. In Argentina, C. chilensis is distributed over the northern two thirds of the country (Prado et al. 2012. Cuad. Herpetol. 26:375–387). Adults are largely herbivorous, but dietary choices may vary according to the available resources (Richard 1994. Cuad. Herpetol. 8:131–140). In Argentina, relationships between nematodes and turtles have received limited attention...